2015
DOI: 10.5350/dajpn2015280404
|View full text |Cite
|
Sign up to set email alerts
|

Relation of anxiety and depressive symptoms with perceived social support according to gender within infertile couples

Abstract: Relation of anxiety and depressive symptoms with perceived social support according to gender within infertile couples Objective: Evaluation of infertile couples' emotional symptoms and perceived social supports according to gender differences.Method: Hospital Anxiety and Depression Scale (HADS) and Multidimensional Scale of Perceived Social Support (MSPSS) were administered to 66 primarily infertile couples that did not have psychiatric Axis-I disorders according to DSM-IV.Results: According to the scale's av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 33 publications
0
20
0
13
Order By: Relevance
“…It has been shown that anxiety is the biggest psychological obstacle for infertile patients ( 29 ). However, social support is an important factor in mitigating the experience of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that anxiety is the biggest psychological obstacle for infertile patients ( 29 ). However, social support is an important factor in mitigating the experience of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that stress from infertility decreases as resources and strategies related to social coping increase ( 30 ). Women with infertility experience more anxiety when they perceive low levels of social support from their partners and other family members ( 29 ). Also, individuals with higher levels of resilience are better equipped to actively apply social coping methods ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Özellikle infertilite nedenindeki belirsizlik, tedavi süresinin bilinmemesi, tedavilerin olumsuz sonuçlanması, tedavinin ekonomik yükü, toplum baskısı gibi nedenlerle psikolojik problemlerin infertil popülasyonda daha sık olduğu görülmektedir (4)(5)(6)(7)(8). Ayrıca çocuk sahibi olamama çiftin her ikisini de etkilemekle birlikte kadınların erkeklerden "daha fazla stres ve sosyal baskı hissettikleri, anksiyete ve depresyon oranlarının daha yüksek olduğu görülmektedir (9)(10)(11). Çünkü infertilite erkeğe ait nedenlerden kaynaklansa bile karmaşık girişimsel tanı-tedavi yöntemlerine ve toplum baskısına kadınlar daha fazla maruz kalmaktadır (8)(9)(10)(11)(12).…”
Section: Introductionunclassified
“…Ayrıca çocuk sahibi olamama çiftin her ikisini de etkilemekle birlikte kadınların erkeklerden "daha fazla stres ve sosyal baskı hissettikleri, anksiyete ve depresyon oranlarının daha yüksek olduğu görülmektedir (9)(10)(11). Çünkü infertilite erkeğe ait nedenlerden kaynaklansa bile karmaşık girişimsel tanı-tedavi yöntemlerine ve toplum baskısına kadınlar daha fazla maruz kalmaktadır (8)(9)(10)(11)(12). Yapılan çalışmaların sonuçları da, infertil çiftlerde erkeklere oranla kadınlarda daha fazla psikiyatrik belirti ve bulgulara rastlandığını göstermektedir (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionunclassified
“…Infertile couples experience chronic stress each month in case of the failure of fertilization 14 . Several researchers have claimed that in the presence of stressors, women use concentrated confrontation on excitement more often compared to men 15 . The findings of one study in this regard indicated that 48% of infertile women and 23.8% of infertile men suffered from depression, while 44% of infertile women were diagnosed with psychological disorders 14 .…”
Section: Introduction:-mentioning
confidence: 99%